First principles calculation on bonding of PT-Fe overlayer and its effects on PT-surface reactivity - Escaño, Mary Clare Sison (Animo Repository, 2008)
First principles spin-polarized total energy calculations using density functional theory (DFT) within generalized gradient approximation (GGA) were performed to investigate the electronic structure of Pt monolayer on Fe(001) and the bonding at Pt-Fe and its effect on O atom chemisorption. Layer-by-layer density of states (DOS) for Pt/Fe(001) against the reference system sunreconstructed Pt(001) and Fe(001) show a peak of Pt d states at the Fermi level and a spin polarization of Pt dzz states. Charge redistribution at Pt-Fe interface shows charge transfer from the Pt and Fe atom sites towards the Pt-Fe bonds verifying strong bimetallic bonding. Similar charge redistribution is observed for Pt(001) with increase in charges at surface Pt-Pt bonding sites. Binding energies of adsorbed O on the three high symmetry sites follow the order: top < hollow < bridge. The efficiency of Pt d-electron back donation to adsorbed O on bridge is driven by a more localized bonding of O atom on this site. Such is explained by the changes in work function (along with Bader charge transfer) of the surface upon O atom adsorption. This mechanism of electron back donation may also be utilized in rationalizing the observed weakened binding of O on Pt/Fe ii system as compared to clean Pt(001) along with the d-band theory.